Growth, Yield, Quality and Insect-Pests in Sugarcane (Saccharum officinarum) as Affected by Differential Regimes of Irrigation and Potash under Stressed Conditions - Rajan Bhatt; Rajinder Kumar; Lenika Kashyap; Abed Alataway; Ahmed Z. Dewidar; Mohamed A. Mattar (Agronomy, 2022)
Land productivity and quality were negatively impacted by both unbalanced fertilization and water-stressed conditions, which has arisen as an important topic of research. In the semi-arid tropics, sugarcane is the main source of sugar and ethanol; however, no potash (K) dose is recommended for the deficient sites in the region, which are further responsible for lower recovery. As a result, in order to standardize the K dose for deficient sites, present experiments carried out during plant (2019–2020) and ratoon (2020–2021) seasons. The statistical design was a split-plot design with main plot treatments comprised of I1 (irrigated) and I2 (stressed) treatments followed by K1, K2, K3, and K4 plots fertilized with 0, 40, 80, and 120 kg K2O ha−1 in subplots. Germination was reported to be 13.7, 25.0 and 32.3% higher during plant and 6.2, 17.3 and 24.4% higher during ratoon season in K2, K3, and K4 plots, respectively. Tiller’s cane−1 was recorded to be significantly affected by potash levels at 241 days after planting (DAP) and 261 and 326 days after harvesting (DAH). Periodic chlorophyll content of the sugarcane leaves was reported not to be affected by irrigation treatments except at 355 DAP and 324 and 357 DAH, where respected values were reported to be 2.06% in the plant season and 1.55 and 2.54% higher in the ratoon season in I1 plots, respectively. During plant season purity and extraction after the 10th month, respective values were reported to be 1.5% lower and 4.03% higher under I1 plots, while only Brix (%) was reported as significant and 2.42% higher in I1 plots during plant season after the 12th month. The incidence of early shoot borer (Chilo infuscatellus) and stalk borer (Chilo auricilius) was reported to be significantly higher under stressed conditions (30.4 and 21.5% lower in I1 plots) during the plant season, while early shoot borer (Chilo infuscatellus), stalk borer (Chilo auricilius) and top (Scirpophaga excerptalis) incidences were significantly lower in I1 plots to the tune of 19.6, 22 and 9.73% as compared to the I2 plots during the ratoon season. The application of 80 kg K2O ha−1 resulted in significantly higher cane yield and decreased insect-pest occurrence. Even though 120 kg K2O ha−1 promoted different plant and ratoon sugarcane characteristics, they were all statistically equivalent. In I1 plots, benefits increased from K2 to K3 plots by 26.7% during plant and 155% during ratoon seasons but decreased from K3 to K4 plots by 21.0% during plant and 26.1% ratoon seasons. In I2 plots, however, benefits from K2 to K3 plots were reported to be 72.7% during plant and 76.5% during ratoon seasons, which was reduced to 10.5% during plant and 16.7% during ratoon seasons in K4 plots. Results of a two-year study on plant and ratoon canes revealed that 80 kg K2O ha−1 at deficient sites significantly improved the performance of both plant and ratoon canes yields, sugar yields, reduced the insect-pests’ incidence, and finally the benefits of the cane farmers under both irrigation regimes.